![{x}^{2} - 6x + 5 = 0 {x}^{2} - 6x + 5 = 0](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B2%7D+-+6x+%2B+5+%3D+0+)
Soluções para a tarefa
Respondido por
1
Olá!!!
Resolução!!!
x² - 6x + 5 = 0
Coeficientes
a = 1, b = - 6, c = 5
bhaskara
∆ = b² - 4ac
∆ = ( - 6 )² - 4 • 1 • 5
∆ = 36 - 20
∆ = 16
∆ > 0 , ah duas raizes reas
x = - b ± √∆/2a
x = - ( - 6 ) ± √16/2 • 1
x = 6 ± 4/2
x' = 6 + 4/2 = 10/2 = 5
x" = 6 - 4/2 = 2/2 = 1
S = { 1, 5 }
Espero ter ajudado!!
Perguntas interessantes
História,
10 meses atrás
Matemática,
10 meses atrás
História,
1 ano atrás
Matemática,
1 ano atrás
Geografia,
1 ano atrás